(untitled) (Faridpur Medical College Journal, 2026)
Background: Bacterial vaginosis diagnosis remains challenging in resource-constrained settings. Point-of-care tests may enable timely management, particularly during pregnancy when bacterial vaginosis-associated complications carry substantial maternal and neonatal risks. Materials and Methods: We conducted a prospective cross-sectional pilot study over two days (February 22–23, 2025) at a high-volume obstetrics-gynecology private clinic in Faridpur, Bangladesh. All pregnant women attending for routine antenatal care were enrolled. Paired vaginal specimens for concurrent BVBlue® rapid testing and standard culture were collected. We assessed bacterial vaginosis prevalence, diagnostic accuracy metrics (sensitivity, specificity, positive and negative predictive values), turnaround time and operational feasibility. Results: Among 37 enrolled participants (median age 26 years, median gestational age 27 weeks), culture-confirmed bacterial vaginosis prevalence was 24.3% (9/37). Against culture as the reference standard, BVBlue® rapid test demonstrated 66.7% sensitivity (95% Confidence Interval [CI] 30.0–90.3), 100% specificity (95% CI 88.1–100.0), 100% positive predictive value (95% CI 56.1–100.0), and 90.3% negative predictive value (95% CI 75.1–96.7). Median turnaround time was 12 minutes for BVBlue® rapid testing versus 60 hours for culture. Reported per-test costs were lower for BVBlue® rapid testing (approximately 12-17 USD) than culture (approximately 20-25 USD). Conclusion: In this pilot evaluation, the BVBlue® rapid test offered rapid, highly specific bacterial vaginosis detection with moderate sensitivity compared with culture. The reduction in turnaround time and reported cost advantage suggest potential utility in resource-limited settings. However, the small sample size, wide confidence intervals, and use of culture rather than the gold standard Nugent scoring as the reference standard necessitate larger validation studies. Faridpur Med. Coll. J. 2026;21(2):07-12